Efforts to Facilitate the Community in Increasing the Learning Interests of the Children of Mekarsari Village to Take Formal Education Through the Educational Counseling Program - Muhammad Al-Mighwar; Danis Muhammad Akbar; Ikhsan Daffa Suparno; Rifa Salsabila (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
KKN Sisdamas (community empowerment system) is the service of students to the community to help existing programs in an area. The Sisdamas KKN organized by UIN SGD Bandung this year has many basic programs such as nationality, tolerance, anti-violence and local culture. This research focuses on basic national and local cultural programs as well as strengthening programs, namely the empowerment of preaching and psychological education. According to history, education has existed for a long time and has been applied in social life by humans. Humans should make education an absolute necessity, because humans can develop and progress as they are now without education. On the other hand, education is a primary need which of course is very functional for the continuity of human life, with education humans can have social relationships and can develop and foster mental readiness which will later shape a person's character. In Indonesia itself, education is regulated by the state and attendance at all levels of education is mandatory for every Indonesian citizen. Early Childhood Education, Primary Education, Secondary Education and Higher Education are the four levels of education in Indonesia. Article 31 paragraphs 1 and 2 of the 1945 Constitution which states that everyone is obliged to be educated and obtain education and the state is obliged to charge fees if there are people who are unable to pay for them, mentions all of that. Because education is regulated in law, of course all citizens must obey and comply with these regulations. However, there are factors that cause citizens to not comply with the rules regarding education, the factor that most often arises is economic factors, with a lack of funds to pursue a complete education, this will give rise to the urge to drop out of school or a lack of interest in studying. In this article, we will discuss measures that can be taken to increase a person's interest in learning and be able to complete education, both formal and non-formal education.